E-Invoicing in Malaysia: evaluating opportunities and challenges for business owners - Shaikh Mohammad, Siti Nor Syahira; Ku Ahmad, Ku Ahmisuhaiti; Hassan, Rahayu (Faculty of Accountancy, 2025)
E-invoices in Malaysia are structured digital documents, typically in XML or JSON format, that undergo real-time validation through the Myinvois platform before being submitted to the Inland Revenue Board (LHDN) for clearance. This Clearance model ensures that each invoice is authenticated and assigned a unique reference number (IRN) before being sent to customers or buyers. Such a mechanism promotes transaction traceability, enhances workflow automation, and aligns closely with national goals for improved tax compliance and digital operational efficiency (LHDN, 2025).